Perceived declining physical and cognitive fitness during the COVID‐19 state of emergency among community‐dwelling Japanese old‐old adults. Issue 4 (11th February 2021) - Makizako, Hyuma; Nakai, Yuki; Shiratsuchi, Daijo; Akanuma, Tomomi; Yokoyama, Kaori; Matsuzaki‐Kihara, Yuriko; Yoshida, Hiroto
Abstract : Aim: Perceived health status, including physical and cognitive fitness, will be negatively associated with future health conditions among old‐old adults. The coronavirus disease 2019 (COVID‐19) pandemic has caused sudden changes in lifestyle. Thus, this study examined the associations of participation in an exercise class before the COVID‐19 pandemic and the exercise habits and disruption to the rhythms of daily life during the COVID‐19 state of emergency with perceived declining physical and cognitive fitness among community‐dwelling old‐old adults. Methods: In July 2020, we carried out a mail survey of community‐dwelling old‐old adults aged between 77 and 99 years in Bibai, Hokkaido, Japan, to determine their perceived declining physical and cognitive fitness during the COVID‐19 state of emergency. Results: Of the 774 responders, 339 (43.8%) participants reported a decline in physical fitness, whereas 259 (33.5%) perceived declining cognitive fitness during the COVID‐19 state of emergency. In a multivariate logistic regression model adjusted for potential confounders, exercise habits during the COVID‐19 state of emergency were significantly associated with a lower perception of declining physical fitness. Disruption to the rhythms of daily life during the COVID‐19 state of emergency was significantly associated with a higher perception of declining physical and cognitive fitness. Conclusions: Approximately half and more than one‐third of community‐dwelling old‐old adults perceived declining physical and cognitive fitness, respectively, during the COVID‐19 state of emergency. During this period, exercise habits were positively correlated with perceived health status among old‐old adults, whereas disruption to the rhythms of daily life was negatively correlated. Geriatr Gerontol Int 2021; 21: 364–369 .